2009
DOI: 10.21608/jfds.2009.115819
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICO-CHEMICAL ASSESSMENT OF NATURAL SWEETENERS STEVIOSIDES PRODUCED FROM STEVIA Rebudiana bertoni PLANT

Abstract: Stevia plants are a good source of carbohydrates (61.93 % d.w.), protein (11.41 % d.w.), crude fiber (15.52 % d.w.), minerals (K, 21.15; Ca, 17.7; Na, 14.93 & Mg, 3.26 mg/100g d.w. and Cu, 0.73; Mn, 2.89; Fe, 5.89 & Zn, 1.26 mg/100g d.w.) also essential amino acids were found in amounts higher than those recommended by FAO and WHO for adults as well as non-essential amino acids. Stevioside was extracted and purified from the dried Stevia leaves by three methods. The first one, extraction by hot water (65 °C) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 11 publications
5
65
0
6
Order By: Relevance
“…The assay was conducted according to the Abou-Arab et al method. [10] The obtained extracts were subjected to multi-wavelength absorbance measurement in the SPECORD S40 apparatus (Analytic Jena, Germany). Absorbance was read for the following wavelengths: 440 nm (A 440 ); 644 nm (A 644 ) and 662 nm (A 662 ).…”
Section: Total Carotenoid and Chlorophyll Contentmentioning
confidence: 99%
“…The assay was conducted according to the Abou-Arab et al method. [10] The obtained extracts were subjected to multi-wavelength absorbance measurement in the SPECORD S40 apparatus (Analytic Jena, Germany). Absorbance was read for the following wavelengths: 440 nm (A 440 ); 644 nm (A 644 ) and 662 nm (A 662 ).…”
Section: Total Carotenoid and Chlorophyll Contentmentioning
confidence: 99%
“…Carbohydrates are the main sources of energy and they are found as structural components of cellular elements (Lemus-Modaca et al, 2012). Carbohydrate contents in dry leaves of sweetleaf ranged from 35.2 to 61.9 g•100 g -1 product (Abou-Arab et al, 2010;Boonkaewwan et al, 2006). Their positive action is connected with prebiotic properties promoting proliferation of benefi cial intestinal microfl ora.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Fat content in dry matter of stevia leaves amounts to 1.9-4.34 g•100 g -1 d.m. (Abou-Arab et al, 2010;Siddique et al, 2014). The chemical composition of this plant is also affected by the method of leaf drying (Gasmalla et al, 2014).…”
mentioning
confidence: 99%
“…Previous studies [ 8 , 9 ] reported that the stevioside exhibits numerous immunoregulation activities and has antibacterial properties, anti-inflammation properties, and maintenance of the blood lipid content. Previous studies showed that the stevia extract contains amino acids, polyphenols, and flavonoids and has antioxidant properties [ 10 , 11 , 12 , 13 ]. A few studies have been conducted on nonruminants, including pigs and poultry [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%